Purinergic receptors as potential therapeutic targets in Alzheimer's disease. (May 2016) - Woods, Lucas T.; Ajit, Deepa; Camden, Jean M.; Erb, Laurie; Weisman, Gary A.
Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by a progressive loss of memory and cognitive ability and is a serious cause of mortality. Many of the pathological characteristics associated with AD are revealed post-mortem, including amyloid-β plaque deposition, neurofibrillary tangles containing hyperphosphorylated tau proteins and neuronal loss in the hippocampus and cortex. Although several genetic mutations and risk factors have been associated with the disease, the causes remain poorly understood. Study of disease-initiating mechanisms and AD progression in humans is inherently difficult as most available tissue specimens are from late-stages of disease. Therefore, AD researchers rely on in vitro studies and the use of AD animal models where neuroinflammation has been shown to be a major characteristic of AD. Purinergic receptors are a diverse family of proteins consisting of P1 adenosine receptors and P2 nucleotide receptors for ATP, UTP and their metabolites. This family of receptors has been shown to regulate a wide range of physiological and pathophysiological processes, including neuroinflammation, and may contribute to the pathogenesis of neurodegenerative diseases like Parkinson's disease, multiple sclerosis and AD. Experimental evidence from human AD tissue has suggested that purinergic receptors may play a role in AD progression and studies using selective purinergic receptor agonists and antagonists in vitro and in AD animal models have demonstrated that purinergic receptors represent novel therapeutic targets for the treatment of AD. This article is part of the Special Issue entitled 'Purines in Neurodegeneration and Neuroregeneration'. Highlights: Alzheimer's disease is a neurodegenerative disorder resulting in loss of cognition. Neuroinflammation is a major component of Alzheimer's disease. Purinergic receptors can regulate neurodegeneration and neuroinflammation. Purinergic receptors are novel drug targets to treat Alzheimer's disease.